Time Course Change in Muscle Swelling: High-Intensity vs. Blood Flow Restriction Exercise - Freitas, Eduardo D.S.; Poole, Christopher; Miller, Ryan M.; Heishman, Aaron David; Kaur, Japneet; Bemben, Debra A.; Bemben, Michael (International Journal of Sports Medicine, 2017)
This study determined the time course for changes in muscle swelling and plasma volume following high (HI) and low-intensity resistance exercise with blood-flow restriction (LI-BFR). Ten male participants (22.1±3.0 yrs) completed three experimental conditions: high-intensity exercise (HI - 80% of 1RM), low-intensity exercise with BFR (LI-BFR –20% of 1RM, and 160 mmHg of BFR), and control (CON – no exercise or BFR). Muscle cross-sectional area (mCSA), muscle thickness, thigh circumference, and percentage change in plasma volume (PV%∆) were measured. mCSA was significantly greater than rest values at 15 min post-exercise (p<0.01) for HI and LI-BFR, and at 75 min post-exercise (p<0.01) for HI. Muscle thickness was significantly greater than rest immediately post-exercise (p<0.01) and 30 min post-exercise (p<0.01) for HI and LI-BFR, and at 60 min post-exercise for HI (p=0.01). Muscle thickness was greater for BFR immediately post-exercise compared to HI (p=0.01) post-exercise. Thigh circumference was significantly greater from rest at 15 min post-exercise (p=0.01) and at 75 min post-exercise for both LI-BFR (p=0.03) and HI (p<0.01). PV%∆ significantly decreased from rest immediately post-exercise for both HI (p<0.01) and LI-BFR (p<0.01). In conclusion, BFR exercise induces changes in muscle swelling and plasma volume similar to those observed at high-intensities.
Keywords: occlusion training; strength exercise; cell swelling; hematocrit; pQCT; ultrasound